Integrative taxonomy and phylogeography of Colomys and Nilopegamys (Rodentia: Murinae), semi-aquatic mice of Africa, with descriptions of two new species. Issue 1 (8th October 2020) - Giarla, Thomas C; Demos, Terrence C; Monadjem, Ara; Hutterer, Rainer; Dalton, Desiré; Mamba, Mnqobi L; Roff, Emily A; Mosher, Frank M; Mikeš, Václav; Kofron, Christopher P; Kerbis Peterhans, Julian C
Abstract: The semi-aquatic African murine genera Colomys and Nilopegamys are considered monotypic and thought to be closely related to one another. Colomys occurs across forested regions of equatorial Africa, whereas Nilopegamys is known only from the Ethiopian holotype, making it among the rarest mammalian genera in the world – and possibly extinct. Using morphological and genetic data, we reassess the taxonomy of Colomys and Nilopegamys . A multilocus phylogeny with outgroups demonstrates that Nilopegamys is sister to Colomys . In addition, we recognize at least four morphologically diagnosable and genetically distinct species within Colomys : C. eisentrauti (elevated from subspecies and restricted to north-west Cameroon), C. goslingi (with a more restricted range than previously reported) and two new species (one from Liberia and Guinea and one from central and southern Democratic Republic of the Congo and Angola). We also review the status of four other taxa currently recognized within Colomys goslingi ( bicolor, denti, goslingi and ruandensis ) and demonstrate that these names lack phylogenetic and/or morphological support. Finally, we discuss potential biogeographic barriers that may have played a role in the evolution of Colomys and Nilopegamys, emphasizing the importance of rivers in both facilitating and, possibly, limiting dispersal within these genera.